Health implications for residents of slums in Baghdad governorate (Al-Muntadhar neighborhood is a case study) - Majeed, Zeinab Yaqoob (Al-Adab Journal, 2015)
The health implications of one of the major problems experienced by the residents of slum areas in Iraq , and has been selected ( The neighborhood Al-Montazer ) in the case of the province of Baghdad as a model to study this phenomenon . And since the health of the community is directly linked to the level of the surrounding environment has been the adoption of elements of environmental sanitation goal sanitation , drinking water , housing health , paved streets , clean surroundings and waste disposal as a measure of the health of the community in the study area . The research and field study , especially the questionnaire as the main source for the data required where the sample included a hundred families in the neighborhood expected . And may reach a search to several conclusions, including , that the poor residential environment and the general environment of the area studied contributed significantly to the spread of many diseases transitional such as viral hepatitis and typhoid and diseases of the digestive tract , such as intestinal colic and diarrhea and intestinal worms and allergic diseases different . As well as the deterioration of the health of the mother and child due to malnutrition caused by the low economic level of families and not being able to meet all the requirements of food , which contributed to the high mortality rate of children under five years of age to 14 % , as well as the neglect of childhood and the deteriorating health of the mother ’s physical and psychological